Early philosophical Shiism the Ismaili Neoplatonism of Abū Yaʻqūb al-Sijistānī - Walker, Paul E. 1941- (Cambridge University Press, 1993)
The Ismailis, among whom are the followers of the Aga Khan, rose to prominence during the fourth Islamic/tenth Christian century. They developed a remarkably successful intellectual programme to sustain and support their political activities, promoting demands of Islamic doctrine together with the then newly imported sciences from abroad. The high watermark of this intellectual movement is best illustrated in the writings of the Ismaili theoretician Abu Yaq́ub al-Sijistani. Using both published and manuscript writings of al-Sijistani that have hitherto been largely hidden, forgotten or ignored, Dr Paul Walker reveals the scholar's major contribution to the development of philosophical Shiism. He analyses his role in the Ismaili mission (da'wa) of that time and critically assesses the major themes in his combination of philosophy and religious doctrine
Keywords: Abū Yaʻqūb al-Sijistānī, Isḥāq ibn Aḥmad / active 10th century; Abū-Yaʿqūb as-Siǧistānī, Isḥāq Ibn-Aḥmad -- ca. 10. Jh. u.Z.; Geschichte; Ismailites / Doctrines / History; Neoplatonism / History; Neuplatonismus; Ismailiten; Philosophie